Dynamics of Covid-19 Vaccine-Hesitancy among Primary Health Care Workers in an Urban City in India: An Exploratory Study - S. Sana Ali; Gowri Iyer; Hemant Mahajan; Nanda Kishore Kannuri (Indian Journal of Public Health)
The health-care workers (HCWs) were one of the vulnerable populations prioritized during the COVID-19 vaccination (COVISHIELD and COVAXIN) campaign. We aimed to estimate vaccine hesitancy and explore influencing factors among 238 HCWs in 21 Urban Primary Health Centres (UPHCs) across Hyderabad during June and July 2021. We used a semi-structured questionnaire and the SAGE determinants of vaccine hesitancy to determine factors underlying vaccine hesitancy and acceptance. A thematic framework was developed to unpack the factors that shaped the perceptions about the COVID-19 vaccine. We found a 17% hesitancy rate, primarily due to concerns about “vaccine-safety.” HCWs were susceptible to misinformation, potentially shaping their views on COVID-19 vaccines. Despite regulatory approval, one in six HCWs in Hyderabad’s UPHCs delayed or refused vaccinations, citing limited “vaccine-safety” information. This underscores the urgent need to address HCW vaccine hesitancy early, given its potential impact on general vaccine acceptance.